Navigating Cultural, Health, and Information Landscapes A User-focused Approach to Immigrant Health in a Nordic Context - Hamed Ahmadinia (Informaatiotutkimus, 2024)
Hamed Ahmadinia’s dissertation in the field of Information Studies, ”Navigating Cultural, Health, and Information Landscapes A User-focused Approach to Immigrant Health in a Nordic Context”, was examined on May 13, 2024, at the Åbo Akademi's Faculty of Social Sciences, Business and Law. Professor Ágústa Pálsdóttir (University of Iceland, Iceland served as the opponent, with Professor Kristina Eriksson-Backa (Åbo Akademi) as the custodian. The dissertation is published in Åbo Akademi's publication archive Doria at https://urn.fi/URN:ISBN:978-952-12-4364-6.